Keynes and the Keynesian revolution: its impact on economic science and the philosophy of economics - Rincón Castillo, Elita Luisa (Frónesis, 2025)
The history of macroeconomics is the history of economic science, although it is true that, in most textbooks, the birth of the so-called modern macroeconomics is identified with the date of publication, 1936, of the General Theory of Economics. occupation, interest and money of John Maynard Keynes, which gave rise to the so-called “Keynesian revolution.” This article aims to analyze the thoughts of Keynes and the Keynesian revolution, as well as the implications for economic science and the philosophy of economics. Keynes is an important figure in the history of economic thought, he has stirred the waters of politics and economic analysis. Keynes was an interesting economist. There is at least a minimal legacy. It is the legacy of an interest in, and an orientation towards, a restoration of macroeconomic theory and the consequent policy that interests both within and outside the professional discipline of economics. Keynes did not live to see the massive influence of his ideas, but politicians, economists, taxpayers, and historians of economic thought have. In this sense, Keynes removed the economic ideas of his time.